2014
DOI: 10.1017/s0954579413000941
|View full text |Cite
|
Sign up to set email alerts
|

Lasting associations between early-childhood temperament and late-adolescent reward-circuitry response to peer feedback

Abstract: Behavioral inhibition, a temperament identifiable in infancy, is associated with heightened withdrawal from social encounters. Prior studies raise particular interest in the striatum, which responds uniquely to monetary gains in behaviorally inhibited children followed into adolescence. Although behavioral manifestations of inhibition are expressed primarily in the social domain, it remains unclear whether observed striatal alterations to monetary incentives also extend to social contexts. In the current study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
83
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(90 citation statements)
references
References 82 publications
(175 reference statements)
6
83
1
Order By: Relevance
“…Finally, one of the biggest challenges in understanding the combined influence of automatic and controlled information-processing strategies for children with BI is to develop paradigms that best mimic the day-to-day challenges faced by children with heightened BI (eg, Guyer et al, 2014). That is, when attention is drawn to potential signs of threat, how are BI children able to quickly and efficiently encode, process, and respond to the complexities of their social environments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, one of the biggest challenges in understanding the combined influence of automatic and controlled information-processing strategies for children with BI is to develop paradigms that best mimic the day-to-day challenges faced by children with heightened BI (eg, Guyer et al, 2014). That is, when attention is drawn to potential signs of threat, how are BI children able to quickly and efficiently encode, process, and respond to the complexities of their social environments.…”
Section: Discussionmentioning
confidence: 99%
“…In a fourth study, Helfinstein et al (2011) extended these findings to show relations between BI and striatal sensitivity to reward feedback. Guyer et al (2014) extended these studies by using a paradigm with high ecological validity to examine striatal sensitivity to social feedback in adolescents with and without a childhood history of BI. In this study, adolescents rated a series of photographs of other adolescents in terms of whether they would or would not like to interact with them in an online chatroom.…”
Section: Reward Processing In Bimentioning
confidence: 99%
“…These ROIs were chosen based on prior studies, including those that use the chatroom task, which show that responses in these regions discriminate between high- and low-value peers and/or positive and negative social feedback, 28,29,50,51 and were defined anatomically. The vlPFC (762 voxels) is comprised of aspects of inferior frontal gyrus and middle frontal gyrus inferior to z=1.…”
Section: Methodsmentioning
confidence: 99%
“…28,49 This paradigm has previously been used to identify dysregulated engagement of brain regions subsumed by corticolimbic and striatal circuits among adolescents with and at risk for social anxiety. 28,29,50,51 Regions that differ between healthy or low-risk and anxious or high-risk youth in this paradigm include the ventrolateral prefrontal cortex (vlPFC) and ventromedial regions of the prefrontal cortex (vmPFC), as well as the fusiform face area (FFA), amygdala (AMY), and striatum. Engagement of these regions, as well as functional connectivity between vlPFC and AMY and between vmPFC and striatum, likely interact to integrate attention, emotion, and corresponding behavioral responses to social situations.…”
Section: Introductionmentioning
confidence: 99%
“…FMRI studies that have included behaviorally inhibited youth find similar fronto-limbic perturbations as those described in youth with SAD. Notably, studies with adolescents with BI have reported increased responses in the amygdalae to negative emotional expressions, differential striatal responses to the anticipation of monetary and social rewards, and during conflict adaptation (when individuals habituate to successively presented contradictory emotional information) ( Bar-Haim et al, 2009;Guyer et al, 2014;Hardee et al, 2013;Helfinstein et al, 2011;Jarcho et al, 2013aJarcho et al, ,b, 2014Pérez-edgar et al, 2007).…”
Section: G Modelmentioning
confidence: 99%